Robert Mundell: Premio Nobel en Economía - Dornbusch , Rudiger (2000)
Robert Mundell, this year's Nobel Prize conforms to this pattern. He is surely the most creative economist in his field in the second half of this century. Despite the fact that his decisive contribution appeared some decades ago, when he was still a young economist, he has passed the three decades test better than most economists and without many rectifications. The Spanish philosopher Spinoza said that poetry is a network with which reality can be caught: Mundell's models are also that: powerful abstractions, which show the bare minimum to clarify the fundamentals of how the economic world works. A great prize for a great teacher.